Răspuns :
4¹⁴-(6×4¹³-2×2²⁶)
=2²⁸-(6×4¹³-2×2²⁶)
=2²⁸-(3×2×4¹³-2×2²⁶)
=2²⁸-(3×2×2²⁶-2×2²⁶)
=2²⁸-(3×2²⁷-2²⁷)
=2²⁸-(3-1)×2²⁷
=2²⁸-2×2²⁷
=2²⁸-2²⁸
=0
[tex]4 {}^{14} - (6 \times 4 {}^{13} - 2 \times 2 {}^{26} )= \\ 2 {}^{28} - (6 \times 4 {}^{13} - 2 \times 2 {}^{26} ) = \\ 2 {}^{28} - (3 \times 2 \times 4 {}^{13} - 2 \times 2 {}^{26}) = \\ 2 {}^{28} - (3 \times 2 \times 2 {}^{26} - 2 \times 2 {}^{26}) = \\ 2 {}^{28} - (3 \times 2 \times 2 {}^{26} - 2 {}^{27} ) = \\ 2 {}^{28} - (3 \times 2 { }^{27} - 2 {}^{27} ) = \\ 2 {}^{28} - (3 - 1) \times 2 {}^{27} = \\ 2 {}^{28} - 2 \times 2 {}^{27} = \\ 2 {}^{28} - 2 {}^{28} = \\ 0[/tex]